A Peptide Vaccine Candidate Tailored to Individuals' Genetics Mimics the Multi-Targeted T Cell Immunity of COVID-19 Convalescent Subjects - Somogyi, Eszter; Csiszovszki, Zsolt; Molnár, Levente; Lőrincz, Orsolya; Tóth, József; Pattijn, Sofie; Schockaert, Jana; Mazy, Aurélie; Miklós, István; Pántya, Katalin; Páles, Péter; Tőke, Enikő R. (Frontiers in Genetics, 2021)
Long-term immunity to coronaviruses likely stems from T cell activity. We present here a novel approach for the selection of immunoprevalent SARS-CoV-2-derived T cell epitopes using an in silico cohort of HLA-genotyped individuals with different ethnicities. Nine 30-mer peptides derived from the four major structural proteins of SARS-CoV-2 were selected and included in a peptide vaccine candidate to recapitulate the broad virus-specific T cell responses observed in natural infection. PolyPEPI-SCoV-2-specific, polyfunctional CD8+ and CD4+ T cells were detected in each of the 17 asymptomatic/mild COVID-19 convalescents’ blood against on average 7 different vaccine peptides. Furthermore, convalescents’ complete HLA-genotype predicted their T cell responses to SARS-CoV-2-derived peptides with 84% accuracy. Computational extrapolation of this relationship to a cohort of 16,000 HLA-genotyped individuals with 16 different ethnicities suggest that PolyPEPI-SCoV-2 vaccination will likely elicit multi-antigenic T cell responses in 98% of individuals, independent of ethnicity. PolyPEPI-SCoV-2 administered with Montanide ISA 51 VG generated robust, Th1-biased CD8+ and CD4+ T cell responses against all represented proteins, as well as binding antibodies upon subcutaneous injection into BALB/c and hCD34+ transgenic mice modeling human immune system. These results have implications for the development of global, highly immunogenic, T cell-focused vaccines against various pathogens and diseases.